Trial Conduct, Baseline Characteristics, and Symptom Burden of Patients in the ARISE Study - Charles L. Daley; James D. Chalmers; Patrick A. Flume; David E. Griffith; Naoki Hasegawa; Kozo Morimoto; Kevin L. Winthrop; Chau-Chyun Sheu; Korkut Avsar; Dario Andrisani; Luigi Ruffo Codecasa; Dayton W. Yuen; et al. (Pulmonary Therapy)
Abstract Introduction ARISE was a global clinical trial designed to generate evidence demonstrating the utility of the patient-reported outcome instruments Quality of Life–Bronchiectasis (QOL-B) [Respiratory Domain (RD) only] and Patient-Reported Outcomes Measurement Information System Short Form v1.0-Fatigue 7a (PROMIS F SF-7a) in patients with newly diagnosed or recurrent Mycobacterium avium complex lung disease (MACLD). Here, we describe trial conduct, patient characteristics, and patient-reported symptoms at baseline among patients enrolled in ARISE. Methods Adult patients with newly diagnosed or recurrent non-cavitary MACLD who had not initiated antibiotic treatment for their current MAC infection were enrolled; data including comorbidities and prior MACLD history were collected during screening. Symptom burden was assessed using QOL-B, PROMIS F SF-7a, and Functional Assessment of Chronic Illness Therapy (FACIT) questionnaires. Results Of 99 patients from 12 countries enrolled in ARISE, the median age was 69.0 years; most were white (80.8%) and female (77.8%). This was the first diagnosis of MACLD for 72.7% of patients. Patients frequently reported having a comorbid respiratory disorder: bronchiectasis (49.5%), asthma (21.2%), and chronic obstructive pulmonary disease (16.2%). At baseline, mean (± SD) and median QOL-B RD scores were 65.0 (± 15.3) and 66.7; PROMIS F SF-7a T-scores were 53.8 (± 8.2) and 55.1; and FACIT-Fatigue scores were 35.0 (± 9.6) and 37.0. Conclusions Patients in ARISE were representative of a real-world patient population with MACLD. Comorbid chronic respiratory diseases were common in patients with new or recurrent MACLD, and substantial disease burden at the time physicians initiated MACLD treatment was evidenced by impairment across measures of fatigue and QOL-B domains. ClinicalTrials.gov Identifier NCT04677543. Graphical Abstract